Evaluation of functional and clinical outcome of open reduction and internal fixation of Barton’s fracture of the wrist in a central hospital of Kashmir - Bhat, Jawed A.; khurseed, Faesal; Javaid, Abdul H. (International Journal of Research in Orthopaedics, 2021)
Background: Fractures of the distal end of radius continue to pose a management challenge. Defective alignment of extra articular as well as intra articular fractures result in a variety of complications like post traumatic arthritis, decreased in grip strength and endurance as well as limited range of motion and instability of carpus. The main aim of this study is to assess the functional results of open reduction and internal fixation in the treatment of volar Barton’s fracture. Methods: From December 2006 to December 2019, forty cases of volar Barton’s fracture were operated in Skims Medical College Hospital, Srinagar, Kashmir, however only 32 cases were included in the study group and 8 cases were lost to follow up. In the majority of our cases the injury was sustained as a result of road traffic accident followed by fall. Majority (24) of the cases were operated within one week of trauma, followed by six in two weeks and two in 3 weeks of time since injury. Results: Functional evaluation was done after a mean follow-up of 28.7 months. Fracture union was achieved within 8 to 12 weeks and excellent results were obtained in 18 cases and 10 cases were categorized as good followed by fair result in 4 cases. Median nerve compression was not observed in any case. Conclusions: Good to excellent result can be achieved after open reduction and internal fixation which restores joint congruity.